Reduction in mydriatic drop size in premature infants. Issue 6 (June 1993) - Wheatcroft, S; Sharma, A; McAllister, J
Abstract : In a prospective study of 26 premature infants, 5 microliters microdrops were compared with standard 26 microliters eye drops of cyclopentolate 0.5% and phenylephrine 2.5%. There was no statistical difference in pupil dilatation. The 5 microliters microdrops have potentially fewer adverse effects in premature infants.